Alocação ótima de equipamentos SVC e TCSC na rede de transmissão de energia elétrica - Sabillón Antúnez, Carlos Francisco [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research proposes a new approach for the problem of SVC and TCSC allocation in a trans- mission system. Since the rising of FACTS in the late 1970s, this type of devices had become a great tool in the search of solutions for the classic power transmission basic limitations. FACTS help to increase the controllability of flow over the lines and at the same time enhance the system stability. So, these devices can help in steady state augmenting the maximum power transfer among regions of the system and also, help in both the transient and dynamic stability of the system. Knowing the benefits that the FACTS provide to a transmission system, it is important to optimize this betterment. Several features must be taken into consideration to find an optimal location for FACTS in transmission systems such as device type, device size, total system power transfer and voltage and reactive power limit violations in the system. This work allocates two types of FACTS devices, the SVC (Static Variable Compensator) and TCSC (Thy- ristor Controlled Series Compensator). In the past, different approaches have been developed aiming to optimally allocate FACTS in a system. These approaches define their optimal loca- tion evaluating the benefits in steady state or the stability enhancement that the FACTS provide to the system. The objective and greatest contribution of this research is to find a solution for the problem of «optimal location of FACTS» that joins, evaluating in one objective function, both the steady state benefits and the dynamic benefits that the device provide to the system in a specific location. The objective function of the optimization model is calculated when a FACTS device is installed in a specific location. Its optimization criteria depend on the overall generation cost, total system losses, investment costs, maximum loading and system's transient stability. PSAT, a Matlab toolbox, is used to run the routines necessary to ...

Esta pesquisa propõe uma nova abordagem para o problema de alocação ótima de dispositi- vos SVC (Static Variable Compensator) e TCSC (Thyristor Controlled Series Compensator) no sistema de transmissão de energia elétrica. Desde o surgimento dos FACTS na década dos anos 70, estes dispositivos tornaram-se em uma importante ferramenta na solução dos proble- mas clássicos da transmissão. Os FACTS ajudam a aumentar a capacidade de controle de fluxo ao longo das linhas e, ao mesmo tempo, a aumentar a estabilidade do sistema. Assim, estes dispositivos podem ajudar a aumentar a transmissão máxima de potência entre as regiões do sistema e também ajudar na estabilidade dinâmica do sistema. Conhecer os benefícios que os FACTS fornecem ao sistema de transmissão é importante para otimizar esse aprimoramento. Várias características devem ser levadas em consideração para encontrar um local ideal para um FACTS no sistema de transmissão, tais como: o tipo do dispositivo, o tamanho do dispo- sitivo, a transmissão de potência do sistema e as violações dos limites de tensão e de potência reativa no sistema. Este trabalho aloca dois tipos de equipamentos FACTS, SVC e TCSC. No passado, diferentes abordagens têm sido desenvolvidas com o objetivo de alocar de forma otimizada FACTS em um sistema. Estas abordagens definem o local ótimo avaliando os bene- fícios, seja em regime permanente ou em estado transitório, que os FACTS proporcionam ao sistema. O objetivo e maior contribuição desta pesquisa é encontrar uma solução do problema de alocação ótima de SVCs e TCSCs que junte, avaliando em uma mesma função objetivo, tanto os benefícios no regime permanente, quanto os benefícios dinâmicos que o equipamento proporciona ao sistema em um determinado local. A função objetivo do modelo de otimização é calculada quando um dispositivo FACTS é instalado num local específico. Os critérios de oti- mização dependem do custo de...
Keywords: Sistemas de energia eletrica; Energia eletrica - Transmissão; Sistemas de energia eletrica - Estabilidade; Controle por tiristores; Electric power systems